Pengaruh Citra Merek, Harga Dan Distribusi Terhadap Keputusan Pembelian Minyak Goreng Sunco (Studi Kasus : Pada Ibu Rumah Tangga di Kota Langsa) - Sari, Indah Permata; Indah, Dewi Rosa; Safrizal, Safrizal (Universitas Labuhanbatu, 2022)
The purpose of this study was to determine the effect of brand image, price, and distribution on purchasing decisions of Sunco cooking oil for housewives in Langsa City. The sample used is 96 respondents. The data analysis method is multiple linear regression analysis, t test, F test, and coefficient of determination test. The regression equation in this study is Y = 3.408 + 0.256X1 + 0.302X2 + 0.391X3. From the t test, it can be explained that brand image, price, and distribution have a significant effect on purchasing decisions. From the F test, it can be explained that brand image, price and distribution have a significant effect on purchasing decisions.